Trump: New Populist or Old Democrat?. Issue 3 (2nd October 2019) - Muravchik, Stephanie; Shields, Jon A.
ABSTRACT: Donald Trump's victory depended on the defection of hundreds of longstanding Democratic communities. Trump appealed to these communities partly because he behaves like some of their most beloved politicians. Like the president, these politicians are brazen, thin skinned, nepotistic, and offer an older, boss-centered vision of politics. Trump—the anti-establishment outsider—appealed to voters in these communities because he resembles the local insiders. This appeal widens an old fault line inside the Democratic Party.